Performance of self-etching adhesives on caries-affected primary dentin treated with glutaraldehyde or silver diamine fluoride - Wolowski, Marcelly Tupan Christoffoli; Grenier, Andressa Mioto Stabile; de Oliveira, Victória Alícia; Anselmi, Caroline [UNESP]; Gibin, Mariana Sversut; de Castro-Hoshino, Lidiane Vizioli; Sato, Francielle; Perez, Cristina; Scheffel, Régis Henke; Hebling, Josimeri [UNESP]; Baesso, Mauro Luciano; Scheffel, Debora Lopes Salles (Elsevier, 2024)
Objectives: to evaluate the quality and stability of adhesive interfaces established by self-etching adhesives on caries-affected primary dentin (CAD) treated with glutaraldehyde (GA) or silver diamine fluoride (SDF). Methods: 42 primary molars were exposed to a microbiological caries-inducing protocol and divided into 6 groups according to the adhesive system (Clearfil SE - CL or FL Bond II - FL) and pretreatment (water, GA or SDF) applied on CAD. One tooth from each group was analyzed for surface modification using infrared spectroscopy. Crowns were restored with resin composite (n = 36) and cut into beams and slices. The beams were subjected to microtensile testing, Raman spectroscopy and SEM after 24 h and 6 months of storage. The slices were analyzed using Micro-Raman spectroscopy to determine the diffusion zone thickness (DZ) in each period. Data were analyzed by ANOVA and Tukey or Kruskal-Wallis and Dunn tests (α = 0.05%). Results: SDF reduced the immediate bond strength for both adhesives. The control groups showed a decrease in BS after 6 months in artificial saliva. GA increased immediate DZ for FL, while SDF had the opposite effect on CL. GA decreased the DZ for FL at 6 months. There was a predominance of adhesive failures with areas of cohesive dentin fractures within control groups. Significance: Modifications caused by dentin surface treatments may directly affect the performance of adhesive systems and the quality and stability of adhesive restorations.
Keywords: Adhesion; Caries-affected dentin; Dental adhesives; Dental caries; Dentin; Glutaraldehyde; Microtensile strength; Primary dentin; Raman spectral analysis